Standard Operational Procedures for Outpatient Pharmacy Services at Dr. Iskak Tulungagung Hospital - Indasah; Inggrid Puspitasari Adikarjo (Journal of Community Engagement in Health, 2025)
Pharmaceutical services are one of the activities in hospitals that support quality health services. One of the ways to managed good medicine is to carry out good medicine dispensing, where the process of preparing and delivering medicines to patients by pharmacist or complement pharmaceutical staff ensures that patients receive the right medicines in the right doses in a safe and effective manner. Therefore, it is necessary to create Standard Operating Procedures for outpatient drug services. The aim of activity is to find out Standard Operating Procedures for outpatient drug services at Dr. Iskak Tulungagung Hospital according to Permenkes 129, 2008). The method used in this activity is presentation regarding Standard Operating Procedures to the management and pharmacy Installation staff at Dr. Iskak Tulungagung Hospital using power point and interactive dialogue. The result of this activity is Standard Operating Procedures for outpatient drug services Dr. Iskak Tulungagung Hospital.